2014
DOI: 10.1371/journal.pone.0089174
|View full text |Cite
|
Sign up to set email alerts
|

Value Assessment of Ecosystem Services in Nature Reserves in Ningxia, China: A Response to Ecological Restoration

Abstract: Changes in land use can cause significant changes in the ecosystem structure and process variation of ecosystem services. This study presents a detailed spatial, quantitative assessment of the variation in the value of ecosystem services based on land use change in national nature reserves of the Ningxia autonomous region in China. We used areas of land use types calculated from the remote sensing data and the adjusted value coefficients to assess the value of ecosystem services for the years 2000, 2005, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Due to LULC changes and urbanization, most of these studies showed moderate to significant decrease in ESV [15,16,28,29,41,43] while others found almost no change [46]. Some studies have also revealed an increase in ESV [47][48][49][50]. Such variations in the services value are of the following reasons.…”
mentioning
confidence: 99%
“…Due to LULC changes and urbanization, most of these studies showed moderate to significant decrease in ESV [15,16,28,29,41,43] while others found almost no change [46]. Some studies have also revealed an increase in ESV [47][48][49][50]. Such variations in the services value are of the following reasons.…”
mentioning
confidence: 99%
“…As such, most of the mixed vegetation around the forests were abandoned while they reforest. Wang et al [45] also observed the cushioning impact of increased forest cover on the total ESV of Ningxia of China. Moreover, the forest becoming patchy due to fragmentation and the influx of other land use types into the forest areas caused deforestation and decreased the overall services the landscape provided in 2016.…”
Section: The Influence Of Land Use Dynamics On Ecosystem Service Delimentioning
confidence: 93%
“…In this approach, the natural ecosystem is proposed to represent one seventh of the actual food production. From 2006 to 2015, the average actual grain production in Dinghai district was 4826 kg/ ha, and the average price for grain (mainly composed of paddy, wheat, maize) was 2.1 Chinese yuan/kg (1 Chinese yuan = $0.16 USD) (Wang et al 2014). One equivalent factor of the ESV is therefore 1447.8 Chinese yuan (1.0*4826*2.1/7).…”
Section: Ecosystem Service Valuesmentioning
confidence: 99%